A Challenging Task: Identifying Patients with Cancer of Unknown Primary (CUP) According to ESMO Guidelines: The CUPISCO Trial Experience. (25th March 2021) - Pauli, Chantal; Bochtler, Tilmann; Mileshkin, Linda; Baciarello, Giulia; Losa, Ferran; Ross, Jeffrey S.; Pentheroudakis, George; Zarkavelis, George; Yalcin, Suayib; Özgüroğlu, Mustafa; Beringer, Andreas; Scarato, Jeremy; et al.
Abstract: Background: CUPISCO is an ongoing randomized phase II trial (NCT03498521) comparing molecularly guided therapy versus platinum‐based chemotherapy in patients newly diagnosed with "unfavorable" cancer of unknown primary (CUP). Materials and Methods: Patients with an unfavorable CUP diagnosis, as defined by the European Society of Medical Oncology (ESMO), and available cancer tissue for molecular sequencing are generally eligible. Potential patients with CUP entering screening undergo a review involving reference histopathology and clinical work‐up by a central eligibility review team (ERT). Patients with "favorable" CUP, a strongly suspected primary site of origin, lack of tissue, or unmet inclusion criteria are excluded. Results: As of April 30, 2020, 628 patients had entered screening and 346 (55.1%) were screen failed. Screen fails were due to technical reasons ( n = 89), failure to meet inclusion and exclusion criteria not directly related to CUP diagnosis ( n = 89), and other reasons ( n = 33). A total of 124 (35.8%) patients were excluded because unfavorable adeno‐ or poorly differentiated CUP could not be confirmed by the ERT. These cases were classified into three groups ineligible because of (a) histologic subtype, such as squamous and neuroendocrine, or favorable CUP; (b) evidence of a possible primary tumor; or (c) noncarcinoma histology. Conclusion: Experience with CUPISCO has highlighted challenges with standardized screening in an international clinical trial and the difficulties in diagnosing unfavorable CUP. Reconfirmation of unfavorable CUP by an ERT in a clinical trial can result in many reasons for screen failures. By sharing this experience, we aim to foster understanding of diagnostic challenges and improve diagnostic pathology and clinical CUP algorithms. Implications for Practice: A high unmet need exists for improved treatment of cancer of unknown primary (CUP); however, study in a trial setting is faced with the significant challenge of definitively distinguishing CUP from other cancer types. This article reports the authors' experience of this challenge so far in the ongoing CUPISCO trial, which compares treatments guided by patients' unique genetic signatures versus standard chemotherapy. The data presented will aid future decision‐making regarding diagnosing true CUP cases; this will have far‐reaching implications in the design, execution, and interpretation of not only CUPISCO but also future clinical studies aiming to find much‐needed treatment strategies. Abstract : Effective therapeutic regimens are lacking for patients with cancers of unknown primary (CUP). This article reports the clinic‐pathological challenges associated with diagnosis of unfavorable CUP in the CUPSICO trial and suggests refinements for diagnostic algorithms.